None to accompany me - Gordimer, Nadine, 1923-2014 (Farrar, Straus and Giroux, 1994)
Nadine Gordimer won the Nobel Prize in Literature (possibly in 1993) not for a specific book but for her work as an author. This book is ficton about a woman lawyer in South Africa. It is about man-woman marriage and about race relationships in that country. The title refers to words of a seventeenth century Japanese poet, BASHO who wrote "None to accompany me on this path: Nightfall in Autumn." Included is an article about the author who died in the northern hemisphere summer of 2014.